2013
DOI: 10.1080/21582041.2013.838296
|View full text |Cite
|
Sign up to set email alerts
|

Training of Vancouver 2010 volunteers: a legacy opportunity?

Abstract: The successful delivery of a mega-sport event depends upon a volunteer workforce. It is often asserted that the training of event volunteers contributes to the creation of a social legacy via the transfer of learning to other volunteer contexts; thereby creating an enhanced volunteer pool after the event that will support the tourism and events industries in the host communities. This article reflects upon the reality of that assertion and argues that in order to achieve legacy both training and development st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 10 publications
2
29
0
Order By: Relevance
“…Thus, even if there is a desire to continue volunteering after a mega-event experience, this does not necessarily mean that it can be converted into long-term volunteering in sports, if the necessary support structures and promotion opportunities are not in place [31]. To this end, in [9], the importance of establishing relationships between event organisers and the wider volunteering infrastructure in the host city is emphasised in order to plan for and capitalise on a volunteering legacy. In their study on the Vancouver 2010 Winter Olympic and Paralympic Games, the authors of [9] concluded 'that had there been more communication about planning for legacy before the Games between VANOC and the community groups represented .…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, even if there is a desire to continue volunteering after a mega-event experience, this does not necessarily mean that it can be converted into long-term volunteering in sports, if the necessary support structures and promotion opportunities are not in place [31]. To this end, in [9], the importance of establishing relationships between event organisers and the wider volunteering infrastructure in the host city is emphasised in order to plan for and capitalise on a volunteering legacy. In their study on the Vancouver 2010 Winter Olympic and Paralympic Games, the authors of [9] concluded 'that had there been more communication about planning for legacy before the Games between VANOC and the community groups represented .…”
Section: Literature Reviewmentioning
confidence: 99%
“…The studies on motivations suggest that the chance of being involved in a unique event and being associated with the Olympic movement are key motivating factors in volunteering for the Olympic Games [14][15][16][17]. Recent research interest on the volunteer legacy of the event has started to emerge, examining how event volunteers could be encouraged to sustain their efforts and volunteer again at similar events or in the community after the Games (e.g., [9,18,19]). However, there is a paucity of research on the social legacies such as volunteering for the Olympic Games compared to other legacy aspects that are more tangible, such as urban regeneration and infrastructure.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers addressed this issue as a significant problem specific to not only nonorganizations and community sectors and also attempted to identify important factors contributing to volunteering retention [2]. In a context consistent with this phenomenon, recent research interest on volunteering has examined how volunteers could be motivated to sustain their efforts [3]. Nichols and Ralston (2014) asserted volunteering motivation enable individuals to sustain their enthusiasm and intent to volunteer in a different context [4].…”
Section: Introductionmentioning
confidence: 99%